Anglicisms as Linguistic Markers of Multiculturality in Modern Military Media Discourse - Shulska, Nataliia; Kostusiak, Nataliia; Yasinska, Oksana; Kriukova, Yuliya; Smal, Oksana; Sydorenko, Maryna (My University, 2025)
The article examines Anglicisms’ functioning in the system of Ukrainian servicemen’ call signs as a special type of unofficial anthroponyms represented in modern military media communication. The research material consisted of the texts of journalistic publications, which used English elements to designate the personal call signs of Ukrainian defenders. The sample of factual material covers about 500 nominations used in the speech of the military, who themselves motivate the origin of their call sign or name the sources of its occurrence in the media narrative. The five most representative thematic groups of unofficial names that arose from English-language borrowings are differentiated: 1) call signs from the technological and information environment; 2) nominations related to the military sphere; 3) unofficial anthroponyms indicating status or authority; 4) names formed from English male and female names; 5) call signs motivated by English-language pop culture. Less common are unofficial anthroponyms of other thematic groups, but they also demonstrate a tendency of assimilating English lexemes and neologisms in military communication. In the media discourse, the desire of journalists and the military themselves to explain the origin of their middle names hasbeen traced, which reveals the personal, cultural, and symbolic dimension of anthroponyms in war. Methods of adapting Anglicisms in call signs include transliteration (transmitting English words in Ukrainian letters without translation), Ukrainian graphictransmission, the use of capital letters as visual markers of strength and belonging to the military community, as well as hybridization a combination of English roots with Ukrainian word-formation models. It is concluded that Anglicisms in the call signs of Ukrainian military personnel act not only as a means of nomination, but also as linguistic markers of multiculturality, reflecting the integration of the Ukrainian language space into the global information context and symbolizing the openness of modern military culture to intercultural dialogue.
Keywords: Anglicism; Multiculturalism; Call Sign; Unofficial Anthroponymy; Media Discourse; Neologism; Russo-Ukrainian War